Pengembangan Media Bulletin Board Display pada Tema 6 Subtema 1 Kelas III SDN 091349 Tigarunggu T.A 2022/2023 - Henrika Damanik; Laurensia Masri Perangin-Angin (Departement of Mathematics Education, 2023)
This research purpose to determine the feasibility, practicality, and effectiveness of using Bulletin Board Display media in thematic learning Theme 6 Sub-theme 1 Learning 1 for class III students at SDN 091349 Tigarunggu. This research is a type of R&D (Research and Development) research that uses the ADDIE model. This research consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were all 25 students of class III SDN 091349 Tigarunggu. Data collection techniques in this study are using interviews, questionnaires, tests, and documentation. The feasibility test was aimed at FIP ​​PGSD UNIMED expert lecturers, the practicality test was aimed at class III teachers at SDN 091349 Tigarunggu, and the effectiveness test was aimed at class III students at SDN 091349 Tigarunggu. The results of research and development of this media are: 1) Learning media Bulletin Board Display on Theme 6 Subtheme 1 Learning 1 is stated to be very valid with a score of 88% for material experts, 66% for media experts in stage I and 88% for material experts in stage II . 2) The teacher's assessment of class III SDN 091349 Tigarunggu was stated to be very practical with a score of 90%. 3) Student responses in carrying out the pre-test and post-test during field trials using Bulletin Board Display media were declared effective with an N-Gain Score of 1 percentage of 71%